L’écriture « contractuelle » du roman français à la première personne au tournant des Lumières - Rabsztyn, Andrzej (Romanica Silesiana)
The present study argues that the French first-person novel, which came into fashion in the Enlightenment period through the adoption of epistolary, diary or memoir forms, or through their admixture in texts, lends itself particularly well to “reading pacts”. The sociopolitical context of the period favored romantic fictions of intimate literature that were attuned to the events of the day. In this paratextual discourse, novelists relied on contemporary events to initiate readers into questions such as the status and the goals of novelistic writing, while attempting to legitimize and to valorize the latter. Key words: Epistolary novel, memoir-novel, Enlightenment period, reading pact.